Enhancing ASEAN's connectivity - ASEAN Roundtable on Enhancing ASEAN's Connectivity (2011 Institute of Southeast Asian Studies); Basu Das, Sanchita; Institute of Southeast Asian Studies (Singapore Institute of Southeast Asian Studies, 2013)
"ASEAN has a goal to create an economic community by 2015. To achieve the goal, connectivity among the member states needs to be given due importance. In 2010, ASEAN adopted the Master Plan on ASEAN Connectivity (MPAC), which looked at physical, institutional and people-to-people connectivity. It pinned down fifteen priority projects which can potentially transform the ASEAN region, providing the conditions for a single market and production base. But MPAC is an expensive initiative, and funding remains a major challenge. The private sector needs to be actively involved as a number of infrastructure projects identified in the MPAC are lacking substantial investment. This book looks at the current state of ASEAN's physical connectivity and challenges in building better infrastructure. It contains a collection of papers that discuss specific issues pertaining to each kind of physical connectivity transportation infrastructure, telecom connectivity, ICT and energy infrastructure. The book concludes with the steps needed to be taken for implementation of the various plans, and policy recommendations."--Publisher description.
Overview. Understanding the MPAC / Sanchita Basu Das -- Current state of ASEAN infrastructure / Nguyen The Phuong -- Building greater connectivity across ASEAN / Michael Yeoh, Ng Yeen Seen, Tilottama Roy -- Transportation, telecom, ICT and energy infrastructure. The development of logistics infrastructure in ASEAN : the comprehensive Asia development plan and the post-AEC initiative / Fukunari Kimura -- Challenges for building better transportation infrastructure linkages across ASEAN : Indonesia's perspectives towards an integrated Asian Economic Community / Bambang Susantono -- Connecting Southeast Asia through broadband / Arne Jeroschewski, Andre Levisse, Lorraine Salazar, Robert Tesoriero, and Shaowei Ying -- The current state of ICT systems across ASEAN / Lee Yu Kit -- ASEAN and ICT : a tale of two cities? / Emmanuel C. Lallana -- Integration of energy infrastructure towards ASIAN's connectivity / Nguyen Manh Hung and Beni Suryadi -- ASEAN energy integration : interconnected power and gas pipeline grids / Tilak K. Doshi -- Implementation and policy recommendations. Mater plan on ASEAN connectivity "from plan to implementation" / Somsak Pipoppinyo -- Conclusion and policy recommendations / Sanchita Basu Das.
In English.
Keywords: ASEAN; Transportation and state -- Southeast Asia -- International cooperation; Information technology -- Southeast Asia -- International cooperation; Energy policy -- Southeast Asia -- International cooperation; Power resources -- Southeast Asia -- International cooperation